2018
DOI: 10.1007/s10792-018-1019-7
|View full text |Cite
|
Sign up to set email alerts
|

Unusual microbiological presentations in polymicrobial post-operative endophthalmitis and their clinical correlations

Abstract: Unusual combinations of organisms in post-operative endophthalmitis can introduce unique clinical characteristics and should specifically be considered in atypical clinical presentations, poor response to standard therapy and unusual recurrence patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 34 S. paucimobilis has been isolated in ophthalmic surgery. 35 In a recent study, K. kristinae was isolated from the postoperative wound of a patient in a tertiary hospital in Sierra Leone. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 S. paucimobilis has been isolated in ophthalmic surgery. 35 In a recent study, K. kristinae was isolated from the postoperative wound of a patient in a tertiary hospital in Sierra Leone. 18 …”
Section: Discussionmentioning
confidence: 99%
“…34 S. paucimobilis has been isolated in ophthalmic surgery. 35 In a recent study, K. kristinae was isolated from the postoperative wound of a patient in a tertiary hospital in Sierra Leone. 18 Antibiotic resistance is a global health problem, as it continues to increase at unparallel scale.…”
Section: Discussionmentioning
confidence: 99%
“…This case responded well to vitrectomy and antibiotics with no further recurrence [ 12 ]. Likewise, Mitra et al reported a case who developed delayed endophthalmitis 1 month after his surgery, who saw complete resolution of his disease with vitrectomy and an intense antibiotics regimen [ 13 ]. Another case has been reported in China, although, the findings remain untranslated [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, this microorganism is known as an opportunistic pathogen that causes pulmonary infection associated with cystic fibrosis [2]. Recently, the reports related to ocular infections have been gradually on the rise, especially regarding endophthalmitis after ocular surgeries [3][4][5][6], including intravitreous injection of anti-vascular endothelial cell growth factor agent [7]. B. cepacia has been reported to contaminate topical anesthetics and has also been detected in a cornea tissue bank for keratoplasty [8], as well as rigid gas permeable trial lenses and lens cases [9].…”
Section: Introductionmentioning
confidence: 99%